2014
DOI: 10.1152/ajpregu.00273.2014
|View full text |Cite
|
Sign up to set email alerts
|

Novel antidiabetic nutrients identified by in vivo screening for gastric secretion and emptying regulation in rats

Abstract: Jordi J, Herzog B, Lutz TA, Verrey F. Novel antidiabetic nutrients identified by in vivo screening for gastric secretion and emptying regulation in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…A few studies in both humans and experimental animals have reported that gastric emptying of tryptophan, administered intragastrically or orally, is slowed compared with control, and in a dose-dependent fashion [ 13 , 14 , 32 ]. Moreover, we have shown that tryptophan, administered intraduodenally, potently stimulates pyloric pressures [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies in both humans and experimental animals have reported that gastric emptying of tryptophan, administered intragastrically or orally, is slowed compared with control, and in a dose-dependent fashion [ 13 , 14 , 32 ]. Moreover, we have shown that tryptophan, administered intraduodenally, potently stimulates pyloric pressures [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Technically, even more demanding than measuring food intake is the quantification of nutrient digestion, as there is no direct optical access to the gastrointestinal tract in most species. More specialized technologies, such as bioluminescence, MRI, or computed tomography, have been valuable to generate insights into in vivo dynamics of digestive function (10,18,19,31). However, all of these methods require immobilization of the experimental subject to reduce motion artifacts, thereby making concurrent behavioral observations impossible.…”
mentioning
confidence: 99%
“…The use of rats as animal models of human gastric emptying and intestinal motility has a long history for healthy or pathological conditions and is routinely used for screening purposes or mechanism investigation. , Similar patterns of nutrients and xenobiotics effects on gastric emptying have been observed between human and rat. ,, Based on this background, a rat experiment of gastric emptying measurement based on a published protocol was selected to study the potential formulation effect on stomach motility.…”
Section: Discussionmentioning
confidence: 99%
“…20 The rat remains the most widely used rodent species in gastrointestinal safety evaluation including gastrointestinal motility assessment. 21 The use of rats as animal models of human gastric emptying and intestinal motility has a long history for healthy 22 or pathological conditions 23 and is routinely used for screening purposes 24 or mechanism investigation. 25,26 Similar patterns of nutrients and xenobiotics effects on gastric emptying have been observed between human and rat.…”
Section: ■ Discussionmentioning
confidence: 99%